Avaliação do desempenho acústico das edificações para fins de financiamento imobiliário - Righi, Paulo César da Rosa (2013)
Most of the Brazilian habitation necessity is supplied by builds financed by real estate institutions. The institutions receive as guarantee the own property financed. Those companies analyze the projects of the enterprises according to technical and professional criteria of its own to the grant of subsidies and comply with the social habitation programs. It was found that, despite the Caixa Econômica Federal is the main financing entity of the real estate business of the country and participating of studies and debates about the validity of the ABNT 15575 norm Housing Buildings Performance, in their analysis to the grant of real estate credit the buildings acoustic parameters are not contemplated yet. Considering that both traffic and neighbors noise bother the people inside their residences it s possible to presume that those buildings do not show a proper performance about acoustic insulation, and, therefore, it isn t complying with of its purpose that is to provide acoustic comfort. The Technical Norms of ABNT NBR 15575, internal normative manuals of the Caixa Econômica Federal, technical documents and studies for the quantification of the acoustic parameters of the buildings were analyzed. In this study acoustic isolation coefficients determined in laboratory and field tests that represent most of the constructive elements used in this country, with data obtained through classical acoustic books and academic works about the subject were used. Were developed a tool composed by 2 electronic worksheets to subsidize the technical analysis of the real estate by the financial institutions in order to ensure that the priority be given to residential enterprises with better acoustic performance. The Worksheet A is about insulation and acoustic insulation, it means, relative to laboratory and field tests and, the Worksheet B is only about acoustic insulation, in other words, relative to field tests. From the report of the worksheets results, will be suggested the creation of one annex to the Caixa Econômica Federal Engineering Analysis Report, in order to contemplate the acoustic performance of the housing and to verify the minimum attendance to the performance norm ABNT 15575, as well as, the attendance level (minimum, intermediate or superior) of the forefront systems, inner seal walls, floor systems and coverage of the housing buildings.